Entre quatro paredes: as políticas (in)visíveis que permeiam o dispositivo clínico psicológico privado - Santos, Ilana Côrtes dos (2023)
This paper aims to map the politics within the private individual psychological clinic. As method, we implemented a bibliographic cartography and we interviewed 9 people who used the psychological device. The topics identified by the literature review have been categorized in four axes: (1) colonizing practices, the movements are aimed at maintaining a hegemonic subjectivity colonized by European standards; (2) psychotechnocracy, these practices seek to promote a universal truth about human beings and their behaviors; (3) capitalization of care, a practice permeated and guided by neoliberal logic; and (4) hope, a proposal for a politicized and transformative clinical practice. In the interviews, as per the logic of intensities, we identified the topics that emerged in their speeches: capitalism, psychologization and individualization, medicalization of life, racism, transphobia and homophobia, patriarchy and sexism, religiosity and hope. We conclude with a discussion about hope as a powerful practice, enabling other possibilities of living beyond the standards and models supported and reaffirmed by the policies exposed here.